Implementation of a Pharmacy Clinical Instructor Model to Facilitate Experiential Learning within Saskatchewan's Entry-to-Practice Doctor of Pharmacy Program - Steven Kary; Cheryl A. Camillo; Shauna Gerwing; Zack Dumont (McMaster University Library Press, 2023)
In response to nationally endorsed changes in pharmacy curricula, the University of Saskatchewan College of Pharmacy and Nutrition (CoPN) sought to expand experiential learning for its pharmacy program. In 2010, Canada's faculties and deans of pharmacy committed to implementing entry-to-practice Doctor of Pharmacy (PharmD) programs in all schools by 2020. The expansion and change in credentialing of Canada's pharmacy training from baccalaureate programs was intended to ensure graduates possess the competencies required within the modern scope of pharmacy practice. To further this transition, the Canadian Council for Accreditation of Pharmacy Programs increased the required hours of students' experiential learning. In Saskatchewan, pre-existing operational and financial pressures on the CoPN, coinciding with the provincial health system's amalgamation from twelve regional health authorities to a single health authority, prompted a collaborative approach. To address the growing need for practical experience within the Saskatchewan Health Authority, the CoPN implemented clinical instructor positions within tertiary care centres in Saskatoon and Regina. This unique approach among PharmD programs provided financial stability and accountability to student learning, although early student feedback identified several challenges with this model. These findings about the clinical instructor model can guide the ongoing implementation of experiential learning within PharmD and other health care professional programs. En réponse aux changements approuvés au niveau national dans les programmes d'études en pharmacie, le College of Pharmacy and Nutrition (CoPN) de l'Université de Saskatchewan a entrepris de multiplier les expériences d'apprentissage de son programme d'études en pharmacie. En 2010, les facultés et les doyens des facultés de pharmacie du Canada se sont engagés à mettre en place des programmes de doctorat en pharmacie (PharmD) dans toutes les écoles à l'horizon 2020. L'expansion et la modification de l'accréditation de la formation en pharmacie au Canada à partir des programmes de baccalauréat visaient à garantir que les diplômés possèdent les compétences requises au regard du champ d'exercice renouvelé de la pharmacie. Pour faciliter cette transition, le conseil canadien pour l'accréditation des programmes de pharmacie a augmenté le nombre d'heures requises pour l'apprentissage par l'expérience des étudiants. Dans la province de Saskatchewan, les tensions opérationnelles et financières préexistantes sur le CoPN, jointes à l'opération de fusion des douze autorités sanitaires régionales du système de santé provincial en une seule autorité sanitaire, ont incité à une approche collaborative. Pour répondre au besoin croissant d'expérience pratique au sein de la Saskatchewan Health Authority, le CoPN a mis en place des postes d'instructeurs cliniques dans les centres de soins tertiaires de Saskatoon et Regina. Cette approche originale parmi les programmes de doctorat en pharmacie a assuré la stabilité financière de l'apprentissage des étudiants et a clairement identifié les responsabilités, même si les premiers retours d'expérience des étudiants ont mis en évidence plusieurs défis liés à ce modèle. Ces résultats concernant le modèle d'instructeur clinique peuvent guider la mise en œuvre continue de l'apprentissage par l'expérience au sein des programmes de doctorat en pharmacie et d'autres programmes professionnels de soins de santé.